Sistem Monitoring Siswa untuk Guru dan Orang Tua Siswa Menggunakan Algoritma Fuzzy C-Means di SD Muhammadiyah Demangrejo - Ardhi Choiruddin; Irfan Pratama (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
SD Muhamaddiyah Demangrejo is an elementary school located in Sentolo, Kulon Progo, Yogyakarta, Indonesia. The student assessment system still uses manual methods or data from students' academic scores are still stored in Microsoft excel, causing the data to be difficult to read. Parents of students receive reports on students' academic scores only when they receive remarks at the middle and end of the semester, causing parents to not be able to see academic scores every day. This study aims to create a system for processing student academic data, with the aim of making it easier for teachers to process grades and making it easier for parents to monitor students' academic grades. In processing academic value data, the researcher uses the Fuzzy C-Means Algorithm. Fuzzy C-Means is clustered where yahoo data is grouped into a data cluster center with the degree of membership of each cluster.